2023
DOI: 10.1002/ps.7364
|View full text |Cite
|
Sign up to set email alerts
|

Residue behavior of cyantraniliprole and its ecological effects on Procambarus clarkii associated with the rice–crayfish integrated system

Abstract: BACKGROUND: Cyantraniliprole, a second-generation diamide insecticide, was recently introduced in China, where the rice-crayfish integrated system (RCIS) is practiced to control rice pest infestations. The aim of this study was to investigate the residue behavior of cyantraniliprole in RCIS and its potential ecological effects on nontarget Procambarus clarkii in order to recommend safe pesticide application strategies.RESULTS: Cyantraniliprole dissipated in rice plants according to first-order kinetics, with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…For example, the 48 h LC 50 of cyantraniliprole for D. magna is 23.9 mg/L, and the chronic toxicity test revealed that the 21 d LC 50 of cyantraniliprole for mobility (13.6 mg/L) could exert lethal and sublethal effects on daphnids . The 96 h LC 50 of cyantraniliprole for juvenile tilapia (Oreochromis mossambicus) was found to be 38.0 mg/L in a previous study, indicating low cyantraniliprole acute toxicity toward tilapia; however, after 28 days of chronic exposure, the tilapia growth rate gradually decreased with increasing cyantraniliprole concentration .…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…For example, the 48 h LC 50 of cyantraniliprole for D. magna is 23.9 mg/L, and the chronic toxicity test revealed that the 21 d LC 50 of cyantraniliprole for mobility (13.6 mg/L) could exert lethal and sublethal effects on daphnids . The 96 h LC 50 of cyantraniliprole for juvenile tilapia (Oreochromis mossambicus) was found to be 38.0 mg/L in a previous study, indicating low cyantraniliprole acute toxicity toward tilapia; however, after 28 days of chronic exposure, the tilapia growth rate gradually decreased with increasing cyantraniliprole concentration .…”
Section: Discussionmentioning
confidence: 91%
“…clarkii per tank (15 L of cyantraniliprole solution or dechlorinated water). Cyantraniliprole concentrations were analyzed using the UPLC-MS/MS detection method established in the previous study …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations